Pandemia da Covid-19 Efeitos no ambiente alimentar de varejo em três municípios da região metropolitana de Belo Horizonte - Heminelly Souza Barroso de Holanda (2023)
Objective: To identify changes in the retail food environment resulting from the covid-19 pandemic, in the year 2020, as well as to analyze the closure of food outlets in the face of the restrictive measures implemented in the metropolitan region of Belo Horizonte-MG. Methodology: Ecological study carried out in three cities in the metropolitan region of Belo Horizonte. Secondary data from the State Department of Finance, the Brazilian Institute of Geography and Statistics, the State Department of Health of the State of Minas Gerais and the Municipal Health Departments were used. The following variables were evaluated: opening and closing of establishments that sold food according to the type and categories of establishments, comparing the restrictive measures implemented in each city with the closure of these establishments. The establishments were classified according to the code of the National Classification of Economic Activities (CNAE), based on the CNAE, the food establishments were classified according to the core activity carried out and the predominance of food sold, being grouped according to the criteria presented in the Technical Report Mapping of Food Deserts for Brazil prepared by the Interministerial Chamber of Food and Nutritional Security (CAISAN), being categorized into three categories, (1) establishments for the acquisition of in natura, (2) mixed establishments, (3) establishments for the acquisition of ultra-processed. Finally, these establishments were aggregated according to the profile of acquisition and consumption of food, being grouped into two categories (1) establishments for immediate consumption, (2) establishments for consumption at home. Furthermore, as this is a study that evaluated the food environment during the Covid-19 pandemic, variables that described the behavior of the pandemic in cities were included in the study, such as the incidence of the disease, mortality rate and legislative measures that were used during the first year of the pandemic. Finally, establishments that closed in 2020 were described according to the vulnerability of the census sector where the establishments were located. Vulnerability was determined by the sector's per capita income (total income/total population), data from the 2010 Population Census were used. Descriptive analysis (relative frequency) was performed using Stata 14.0 software and maps using QGIS software 2.10.1. Results: Among the establishments that closed during the first year of the pandemic, most sold food for immediate consumption (Belo Horizonte 76.53%; Betim 69.95% and Contagem 70.87%). In addition, it was possible to notice an increase in the opening of delivery establishments in the three cities of the study. Despite this, the general characteristics of the retail food environment remained unchanged in the three cities, with high availability of establishments that predominantly sold ultra-processed foods. Conclusion: The Covid-19 pandemic seems to have had a greater impact on establishments that sell food for immediate consumption. However, it is still not possible to state the dimension of the impact generated by the pandemic, for which long-term monitoring is necessary to identify whether there is a remodeling of the food environment.